miR-4711-5p regulates cancer stemness and cell cycle progression via KLF5, MDM2 and TFDP1 in colon cancer cells - Morimoto, Yoshihiro (Br J Cancer, 2020)
BACKGROUND: It is important to establish cancer stem cell (CSC)-targeted therapies to eradicate cancer. As it is a CSC marker, we focused on Kruppel-like factor 5 (KLF5) in this study. METHODS: We searched for candidate microRNAs (miRNAs) that inhibited KLF5 expression by in silico analyses and screened them in colon cancer cell lines. RESULTS: We identified one promising miRNA, miR-4711-5p, that downregulated KLF5 expression by direct binding. This miRNA suppressed cell proliferation, migration and invasion ability, as well as stemness, including decreased stem cell marker expression, reactive oxygen species activity and sphere formation ability. MiR-4711-5p inhibited the growth of DLD-1 xenografts in nude mice with no adverse effects. We found that miR-4711-5p provoked G1 arrest, which could be attributed to direct binding of miR-4711-5p to TFDP1 (a heterodimeric partner of the E2F family). Our findings also suggested that direct binding of miR-4711-5p to MDM2 could upregulate wild-type p53, leading to strong induction of apoptosis. Finally, we found that miR-4711-5p had a potent tumour-suppressive effect compared with a putative anti-oncomiR, miR-34a, in tumour cell cultures derived from five patients with colorectal cancer. CONCLUSIONS: Our data suggest that miR-4711-5p could be a promising target for CSC therapy.